Researching the problems of digital economy development as an indicator of the information society: potential threats and prospects - Hlazova, Anna (Technology audit and production reserves, 2021)
The object of the paper is peculiarities of digital economy development in the framework of informatization of socio-economic, socio-cultural relations. It contributes to the in-depth development of the noosphere, the emergence of new industries and a qualitative transformation of production and distribution relations. The paper examines the impact of digitalization on transformational changes in the economy. As noted at the 14th G20 Summit, the main goals of digitalization are the development of innovations, focused on the development of society 5.0, ensuring the free flow of data and at the same time solving problems, related to information security and the protection of intellectual property rights, as well as bridging the digital gap and promoting the digitalization of micro, small and medium-sized enterprises and the development of smart cities. The research methodology is based on theoretical and methodological analysis of the literature, statistical, comparative analysis, as well as synthesis, generalization and systems analysis. The study has revealed differences between the national approach and world experience in the interpretation of digitalization. For instance, in Ukraine the phenomenon involves, first of all, «digitization» in the field of data collection and analysis. At the same time, the concept of digitalization in developed countries is considered as the modernization of the manufacturing sector based on the implementation of information and communication technologies in order to reduce the capital and material intensity of products to increase competitiveness. In addition, the level of development of central bank digital currencies (CBDC) as one of the indicators of the information society has been analyzed. As a result, it was found, that about 80 % of all central banks in the world have been working on projects to issue their own digital currency. The basic requirements for national CBDC have been systematized. The practical significance, presented in the paper, lies in making recommendations for policy implementation of national economy digitalization. It is important, first of all, to «digitize» the real manufacturing sector, but not only create all sorts of «remote access services», clearly define the government position on cryptocurrencies and continue to implement the project of e-hryvnia (digital currency of National Bank of Ukraine) introduction.